The Self-Service Data Roadmap - Uttamchandani, Sandeep, 1979- (O'Reilly Media, Inc., 2020)
The world's most valuable resource is data. Companies across all industry verticals are using data-driven insights as a key competitive advantage. But the time required for transforming raw data to insights can take days or weeks when you want it in minutes or hours. Data scientists spend nearly 80% of their time in data engineering, rather than developing insights. And most organizations can't scale their data science teams fast enough to keep up with growing business needs for better, faster insights. This book will help data engineers, data scientists, and data team managers address these issues by building a self-service data science platform that democratizes the ability to extract insights from the data to everyone in the organization. Data scientists, software engineers, product managers, and marketers can use it to discover, transform, and analyze data and publish automated insights in production. This book is not: A deep dive into the "shiny new" technologies, or any one specific technology A silver bullet technology for building a self-service portal. Organizations differ in their maturity, people, process, and technology and require tailored solutions This book is: A collection of must-have operational capabilities for building a self-service data portal A blueprint for achieving better and faster insights A process for democratizing data engineering expertise across an organization A practical and indispensable guide for any decision-maker, implementer, or strategist working with an organization's data science platform